Discover New Zealand - Rawlings-Way, Charles (Footscray, Vic. ; London : Lonely Planet, 2012)
Experience The Best of New Zealand. Geothermal Rotorua, scenic Queenstown, vibrant Auckland we've selected the most iconic sights and incredible places so you can enjoy the real New Zealand with the minimum of fuss. Highlights reveal the must-see attractions and unbeatable experiences. Itineraries make planning your trip simpler than ever.
"Experience the best of New Zealand"-- Cover.
"With pull-out map"-- Spine.
Includes bibliographical references and index.
Keywords: New Zealand -- Guidebooks; New Zealand -- Description and travel